TRANSGRESSIVE AND REGRESSIVE SEISMIC FADES OF THE DANUBE DEEP-SEA PALEOFAN - Moskalenko V.N. (My University, 2001)
Based on the seismostratigraphic analysis and geological interpretation of seismic profiling data, three marker surfaces corresponding to structural unconformities and erosion events are defined in the area of the Danube and Dnieper deep-sea fans in the Black Sea continental slope. It is established that sedimentary complexes concurrent to Quaternary glaciations correspond to three main phases in the Black Sea regressions and transgressions.
Keywords: Danube; Dnieper; Black Sea continental slope; Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная